Zambia : Technical Assistance Report-Report on Government Finance Statistics. (IMF Staff Country Reports; Country Report, 2020)
In response to a request from the authorities and as part of the United Kingdom's Department for International Development (DFID) Enhanced Data Dissemination Initiative (EDDI) 2 project, a Government Finance Statistics (GFS) mission visited Lusaka, Zambia, during November 19-30, 2018. This was the third mission to Zambia under the DFID EDDI2 project, following the March 2016 and November 2017 missions. The mission worked essentially with staff at the Zambia Central Statistical Office (CSO) Public Finance Unit (PFU), but also had meetings with staff from the Ministry of Finance's Accountant General, Budget, Investment and Debt Management, and Economic Management departments.